Gender Stereotypes and Entrepreneur Financing - Hebert, Camille (Review of Financial Studies, 2026)
Abstract I document a significant gender gap in entrepreneurs’ access to early-stage equity financing. Using unique administrative data on French startups, I show that this gap is particularly pronounced in male-dominated sectors. Controlling for a comprehensive set of entrepreneur and startup characteristics—including demographics, backgrounds, and motivations—accounts for 42% of the average gender gap. However, in male-dominated sectors, 80% of the gap remains unexplained. Growth-oriented female entrepreneurs rely more heavily on bank loans, substituting equity with debt. Finally, VC-backed female-founded startups outperform their male counterparts in male-dominated sectors. These findings suggest that context-dependent stereotypes influence equity financing decisions.